On little known deep-sea skate Bathyraja abyssicola (Gilbert, 1896) from the waters of Russia - Vladimir N. Dolganov; Talija T. Ginanova (Известия ТИНРО)
Morphological description is given for 38 specimens of rare skate Bathyraja abyssicola caught in the North-West Pacific in the 1974-1989, including juveniles and adults of both sexes. Counts for teeth, vertebras, pectoral fin, and intestinal valve are presented. The species biology is discussed.